A Correlation Between Perception and Health Literacy with Medication Adherence in Patients with Pulmonary Tuberculosis in Kaur Regency in 2025 - Felia Novita Sari; Fikitri Marya Sari; Retni Retni (Student Scientific Journal, 2026)
Background: Mycobacterium tuberculosis is the bacterium that causes tuberculosis (TB) in humans. Although it can affect other organs, the majority of TB bacteria attack the lungs. Based on TB cases in 2024, from January to February 2025, there were 17 cases at Bintuhan Health Center and 21 cases at Linau Health Center, all of which were treated immediately. (Profile of the Kaur District Health Office, 2024). Objective: The objective of this study is to determine the relationship between perception and health literacy with medication adherence in pulmonary TB patients in Kaur Regency. Methods: The research design used is cross-sectional. The population for this study consists of all pulmonary TB patients in Kaur Regency, totaling 38 patients. The samples were taken using the Total Sampling technique. The results of the study are presented in univariate and bivariate analysis with a chi-square test at α 5%. Research results: The research findings indicate a relationship between perception and medication adherence in Kaur Regency, p=(0.003). There is also a relationship between health literacy and medication adherence in Kaur Regency, p=(0.001). Conclusion : It is recommended that the findings of this study serve as additional data for health centers to evaluate and improve infectious disease programs, particularly pulmonary TB.